IGFBP7 Concentration May Reflect Subclinical Myocardial Damage and Kidney Function in Patients with Stable Ischemic Heart Disease - Anna Lisowska; Anna Szyszkowska; Małgorzata Knapp; Magda Łapińska; Marcin Kondraciuk; Inga Kamińska; Tomasz Hryszko; Katarzyna Ptaszyńska-Kopczyńska; Karol Kamiński (Biomolecules, 2022)
The objective of this study was to determine the associations between insulin-like growth-factor-binding protein 7(IGFBP7) concentrations and concentrations of troponin T(TnT), N-terminal pro-B-type natriuretic peptide(NT-proBNP) and the parameters of kidney function in patients with stable ischemic heart disease(IHD). The IHD group consisted of 88 patients, and the population group comprised 66 subjects without a history of IHD. IGFBP7, TnT and NTproBNP concentrations were measured. The IGFBP7 value was considerably higher in the IHD group (1.76 ± 1 ng/mL vs. 1.43 ± 0.44 ng/mL, respectively, p = 0.019). Additionally, IHD subjects had a significantly higher concentration of TnT and NTproBNP. In both groups there was a significant correlation between IGFBP7 and serum parameters of kidney function (creatinine concentration: population gr. r = 0.45, p < 0.001, IHD gr. r = 0.86, p < 0.0001; urea concentration: population gr. r = 0.51, p < 0.0001, IHD gr. r = 0.71, p < 0.00001). No correlation between IGFBP7 and microalbuminuria or the albumin to creatinine ratio in urine was found. Moreover, there was a significant correlation between IGFBP7 concentration and markers of heart injury/overload-TnT and NT-BNP(r = 0.76, p < 0.001 and r = 0.72, p < 0.001, respectively). Multivariate regression analysis in joint both revealed that the IGFBP7 concentration is independently associated with urea, creatinine and TnT concentrations (R2 for the model 0.76). IHD patients presented significantly higher IGFBP7 concentrations than the population group. Elevated IGFBP7 levels are associated predominantly with markers of kidney function and myocardial damage or overload.